Characteristics of latex medical glove usage among health personnel and association with latex allergy - Luengtongkam, Chawapon; Chaiear, Naesinee; Ngamchokwathana, Chatpong; Sakdapipanich, Jitladda; Karoonboonyanan, Wisansanee; Klangka, Paneukkaew; Khammanthoon, Sukanya (Journal of Medicine and Health Sciences, 2025)
Latex medical gloves have been shown to induce Type I hypersensitivity latex allergy (latex allergy symptoms), with significant contributing factors including personal factors and glove usage characteristics. However, studies from Thailand and Southeast Asia are relatively limited. This study aimed to investigate the characteristics of glove usage among health personnel associated with the development of latex allergy symptoms. This study was a cross-sectional analytical epidemiological study utilizing secondary data, including 45 health personnel with and 343 without probable symptoms of latex allergy. Data were collected from databases of self-administered questionnaires, which included variables on glove usage characteristics and latex allergy symptoms. The analysis was conducted using descriptive statistics and multiple logistic regression. The results indicated that the group with probable symptoms of latex allergy had a significantly higher proportion of health personnel with a history of hand dermatitis (p < 0.001), atopic diseases (p = 0.004), and usage of gloves with high extractable protein weight (p = 0.002) compared to those without probable symptoms of latex allergy. Personal factors and glove usage characteristics associated with probable symptoms of latex allergy included: atopic diseases (Adjusted OR = 2.34, 95% CI:1.03, 5.35), history of hand dermatitis (Adjusted OR = 2.66, 95% CI:1.27, 5.57), use of powdered latex gloves (Adjusted OR = 2.31, 95% CI:1.61, 8.71), and use of gloves with high extractable protein weight (Adjusted OR = 2.21, 95% CI: 1.08, 4.58). The analysis of factors contributing to definite symptoms of latex allergy revealed that gloves with high extractable protein weight were statistically significantly associated with definite symptoms of latex allergy (Adjusted OR = 2.36, 95% CI: 1.98, 6.20). When the analysis was conducted only on the subgroup without a history of dermatitis, gloves with high extractable protein weight remained statistically significantly associated with definite symptoms of latex allergy (Adjusted OR = 5.67, 95% CI: 1.59, 37.0). In conclusion, the main factor contributing to the development of latex hypersensitivity symptoms among tertiary-level health personnel in hospitals was the utilization of high extractable protein weight medical latex gloves.